2020
DOI: 10.1371/journal.ppat.1008395
|View full text |Cite
|
Sign up to set email alerts
|

Baloxavir treatment of ferrets infected with influenza A(H1N1)pdm09 virus reduces onward transmission

Abstract: Influenza viruses cause seasonal outbreaks and pose a continuous pandemic threat. Although vaccines are available for influenza control, their efficacy varies each season and a vaccine for a novel pandemic virus manufactured using current technology will not be available fast enough to mitigate the effect of the first pandemic wave. Antivirals can be effective against many different influenza viruses but have not thus far been used extensively for outbreak control. Baloxavir, a recently licensed antiviral drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…The model may have utility in future studies for evaluating residual virus burden following antiviral treatment and thus the potential for transmission. 35 Symptom resolution was faster with baloxavir marboxil than placebo, but not oseltamivir phosphate, in type A virus infections. 25 , 34 These clinical findings suggest that our PK/PD analysis based on virus titre reduction in the murine model could be useful in predicting potent viral load reduction in patients, but might be limited in predicting a shorter time to symptom resolution in otherwise healthy influenza patients.…”
Section: Discussionmentioning
confidence: 96%
“…The model may have utility in future studies for evaluating residual virus burden following antiviral treatment and thus the potential for transmission. 35 Symptom resolution was faster with baloxavir marboxil than placebo, but not oseltamivir phosphate, in type A virus infections. 25 , 34 These clinical findings suggest that our PK/PD analysis based on virus titre reduction in the murine model could be useful in predicting potent viral load reduction in patients, but might be limited in predicting a shorter time to symptom resolution in otherwise healthy influenza patients.…”
Section: Discussionmentioning
confidence: 96%
“…Children and adolescents play a major role in influenza transmission in the household. Our ferret study has shown a possibility of interrupting onward transmission with baloxavir treatment [ 17 ], and a clinical trial in a household-based transmission (ClinicalTrials.gov: NCT03969212) is underway to determine to what extent treatment can reduce the risk of transmission to close contacts.…”
Section: Discussionmentioning
confidence: 99%
“…26 More recently, the potential of BXM to impact influenza virus transmission was assessed in ferrets experimentally infected with influenza A (H1N1) pdm09 virus. 28 The authors reported that administration of a single dose of BXM (4 mg/kg) reduced viral shedding in the upper respiratory tract of ferrets compared to placebo and also reduced the frequency of airborne and contact transmission of virus to healthy ferrets, even when treatment was delayed until 2 days p.i. 28…”
Section: Activity Of Bxa Against Influenza Viruses In Animal Studiesmentioning
confidence: 99%